2021
DOI: 10.1093/molbev/msab270
|View full text |Cite
|
Sign up to set email alerts
|

Selection on Accessible Chromatin Regions inCapsella grandiflora

Abstract: Accurate estimates of genome-wide rates and fitness effects of new mutations are essential for an improved understanding of molecular evolutionary processes. Although eukaryotic genomes generally contain a large non-coding fraction, functional non-coding regions and fitness effects of mutations in such regions are still incompletely characterized. A promising approach to characterize functional non-coding regions relies on identifying accessible chromatin regions (ACRs) tightly associated with regulatory DNA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…Therefore, natural selection is expected to be prevalent in species with large N e , and relaxed in species with small N e . Consistent with this expectation, high levels of adaptive divergence have been detected in species with large N e , for example, Drosophila ( Bierne and Eyre-Walker 2004 ), rodents ( Halligan et al 2010 ), poplar ( Lin et al 2018 ), oaks ( Liang et al 2021 ), and the outcrossing crucifer Capsella grandiflora ( Slotte et al 2010 ; Williamson et al 2014 ; Josephs et al 2017 ; Horvath et al 2021 ), whereas low levels of adaptive divergence are found in hominids ( Eyre-Walker and Keightley 2009 ) and Arabidopsis thaliana ( Foxe et al 2008 ; Hämälä and Tiffin 2020 ), which have small N e . A positive correlation between the rates of adaptive evolution and N e was also observed in plants and animals, suggesting significant effects of N e in determining the level of adaptive divergence ( Strasburg et al 2011 ; Galtier 2016 ; Nam et al 2017 ).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Therefore, natural selection is expected to be prevalent in species with large N e , and relaxed in species with small N e . Consistent with this expectation, high levels of adaptive divergence have been detected in species with large N e , for example, Drosophila ( Bierne and Eyre-Walker 2004 ), rodents ( Halligan et al 2010 ), poplar ( Lin et al 2018 ), oaks ( Liang et al 2021 ), and the outcrossing crucifer Capsella grandiflora ( Slotte et al 2010 ; Williamson et al 2014 ; Josephs et al 2017 ; Horvath et al 2021 ), whereas low levels of adaptive divergence are found in hominids ( Eyre-Walker and Keightley 2009 ) and Arabidopsis thaliana ( Foxe et al 2008 ; Hämälä and Tiffin 2020 ), which have small N e . A positive correlation between the rates of adaptive evolution and N e was also observed in plants and animals, suggesting significant effects of N e in determining the level of adaptive divergence ( Strasburg et al 2011 ; Galtier 2016 ; Nam et al 2017 ).…”
Section: Introductionmentioning
confidence: 71%
“…Evidence that rare variants have a great impact on gene expression suggests that pervasive purifying selection has acted on cis -acting regulatory variants in humans ( Hernandez et al 2019 ). The strength of positive and negative selection varies among species ( Gossmann et al 2010 ; Grivet et al 2017 ; Lin et al 2018 ; Zhao et al 2020 ), and also varies across different portions of the genome ( Williamson et al 2014 ; Josephs et al 2017 ; Uricchio et al 2019 ; Horvath et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies of environmentally responsive genes have discovered a wide range of expression responses (Hodgins-Davis and Townsend, 2009), many populations and species have reacted consistently to environmental stress (He et al, 2021; Lowry et al, 2013; Wos et al, 2021a; Yeaman et al, 2014). As gene expression is primarily controlled by regulatory elements acting either in cis (affecting nearby genes) or trans (affecting distant genes), the conserved expression responses are indicative of conserved regulatory systems (Horvath et al, 2021; Lu et al, 2019; Rodgers-Melnick et al, 2016). Such consistently expressed genes have also shown signals of strong purifying selection at the coding regions (Hodgins et al, 2016; Hunt et al, 2013; Lasky et al, 2014; Lowry et al, 2013; Zhang et al, 2017), suggesting that the regulatory conservation is frequently coupled with the conservation of the gene product.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies of environmentally responsive genes have discovered a wide range of expression responses (Hodgins-Davis and Townsend, 2009), many populations and species have reacted consistently to environmental stress (He et al, 2021;Lowry et al, 2013;Wos et al, 2021a;Yeaman et al, 2014). As gene expression is primarily controlled by regulatory elements acting either in cis (affecting nearby genes) or trans (affecting distant genes), the conserved expression responses are indicative of conserved regulatory systems (Horvath et al, 2021;Lu et al, 2019;Rodgers-Melnick et al, 2016).…”
Section: Introductionmentioning
confidence: 99%